An Interactive Online Interprofessional Opioid Education Training Using Standardized Patients - Connie M. Remsberg; Barbara Richardson; Brenda S. Bray; Marian Wilson; Rie Kobayashi; Tracy Klein; Jennifer Anderson; Sarah Peterson; Carrie Gigray; Dawn DeWitt (MedEdPORTAL, 2023)
Introduction Opioid pain management is complex and requires a collaborative approach. To prepare health professions students to care for patients who have chronic pain, we developed an interprofessional education (IPE) session for delivery using a virtual platform that featured a standardized patient (SP) interaction. Methods The SP case highlighted a patient on opioids for chronic low back pain resulting from a car accident. Despite no improvement in pain or function, the patient continued taking opioids and developed behaviors that could represent opioid misuse. During the synchronous, online session, interprofessional teams of students interviewed an SP and collaborated to develop a holistic care plan to address the patient's pain and potential opioid misuse. The session evaluation included pre- and postsession surveys. Results Over 750 students from medicine, pharmacy, nursing, and social work programs participated in the virtual IPE sessions during a single year. Students rated the session positively. Matched survey responses suggested improved confidence in knowledge and skills, and learning through Zoom was rated favorably. Discussion We successfully implemented a synchronous online IPE session involving SP interactions that allowed students to practice team-based care of a patient with chronic pain who was taking opioids. Based on the success of this IPE session, including the success of the online delivery model, future IPE sessions will continue virtually.